Odpowiedzi

2009-12-04T20:15:47+01:00
A) 7(x²- 3x -2) - 3(x² -6x +1) =7x²-21x -14 -3x² +18x -3 =
= 4x² -3x -17
dla x =-0,2
(-0,2)² -3*(-0,2) -17 = 0,04 + 0,6 - 17 = -(17 -0,64) = -16,36
b)
x(3xy - y) - y(x² - xy + x) =3x²y -xy -x²y +xy² -xy =2x²y -2xy+xy²
dla x = -1 oraz y = 1/5
2*(-1)²(1/5) -2*(-1)(1/5) + (-1)(1/5)² =
= 2/5 + 2/5 - 1/25 =4/5 - 1/25 = 20/25 - 1/25 = 19/25 =0,76
2009-12-04T20:17:22+01:00
7(x²-3x-2)-3(x²-6x+1)=7x²-21x-14-3x²+18x-3=4x²-3x-17

4x²-3x-17 dla x= - 0,2
4(- 0,2)²-3(- 0,2)-17 =4×0,04+0,6-17=-16,24


b)
x(3xy-y)-y(x²-xy+x)=3x²y-xy-x²y+xy²-xy=2x²y+xy²-2xy

2x²y+xy²-2xy dla x= -1, y=⅕

2×(-1)²×⅕+(-1)×(⅕)²-2×(-1)×⅕=2/5-1/25+2/5=10/25-1/25+10/25=19/25=0,76